(untitled) (Colombia Medica, 1988)
In a two-year study conducted at the family medical service at the University of Valle, Cali, Colombia, 284 family medical histories, which included 1032 patients, were studied to detect the mortality and the prevention measures taken to preserve the patient’s health. During this period, it was found that diabetes mellitus had a detection index of 99.3%, and arterial hypertension had a detection index of 84%. The obstetric risk was high in 20% of the patients. The average weight for newborn babies was 3200g without perinatal deaths. In September, 1986, when the family medical service started functioning, the families chosen for the study had a higher proportion of undernourished children. The highest incidence of undernourishment was found within the teacher’s group (26.9%). In August 1988, malnutrition decreased within all groups with the most impact observed within the teacher’s group (6.4%) (p < 0.001). Respiratory tract allergies (RTA) were found in 13% of the selected patients; the worker’s group was the most affected (44%). Family dysfunction was associated with 43.3% of the patients with allergies, increasing to 78.2% in families that had 2 or 3 cases of RTA. Furthermore, it was found that 9.8% of the patients with RTA had Giardia lambia in their feces samples. The stressful events associated with RTA and G. lamblia in 84.6% of patients had these three conditions simultaneously (p < 0.001). Using proper instruments for family practices within a stable population has given continuous attention, emphasizing all levels of prevention and considering the family as an epidemiological unit.